2010
DOI: 10.1007/s00221-010-2294-3
|View full text |Cite
|
Sign up to set email alerts
|

Are functional deficits in concussed individuals consistent with white matter structural alterations: combined FMRI & DTI study

Abstract: There is still controversy in the literature whether a single episode of mild traumatic brain injury (MTBI) results in short-term functional and/or structural deficits as well as any induced long-term residual effects. With the inability of traditional structural brain imaging techniques to accurately diagnosis MTBI, there is hope that more advanced applications like functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) will be more specific in diagnosing MTBI. In this study, 15 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(123 citation statements)
references
References 41 publications
7
113
1
2
Order By: Relevance
“…1,10,15,16 These reports have demonstrated white matter abnormalities in patients with mTBI relative to controls [17][18][19] ; however, these differences have not correlated with symptoms. 20 Similarly, attempts to correlate structural injuries with postconcussive cognitive perfor- mance have shown mixed results without a strong anatomic/ pathologic correlation, with deficits detected in regions as diverse as the occipital cortex and corticospinal tracts.…”
Section: Discussionmentioning
confidence: 96%
“…1,10,15,16 These reports have demonstrated white matter abnormalities in patients with mTBI relative to controls [17][18][19] ; however, these differences have not correlated with symptoms. 20 Similarly, attempts to correlate structural injuries with postconcussive cognitive perfor- mance have shown mixed results without a strong anatomic/ pathologic correlation, with deficits detected in regions as diverse as the occipital cortex and corticospinal tracts.…”
Section: Discussionmentioning
confidence: 96%
“…Cubon et al 31 reported that college athletes with mild TBI (5 men and 5 women) who had concussion showed significantly increased MD in the left hemisphere, spanning the sagittal striatum, retrolenticular section of the internal capsule, and the posterior thalamic radiation (by use of tract-based spatial statistics), but there was no significant change in FA. In a recent study, Zhang et al 32 found no significant differences in fMRI and DTI results among patients with mild TBI versus control subjects; the authors suggested that these regional variations in FA and MD changes in patients with mild TBI might be the result of differing timeframes, technological issues involved in DTI, and different methodologic approaches.…”
Section: Discussionmentioning
confidence: 98%
“…10 In an effort to establish differences between the functionality of fMRI and DTI in the setting of mTBI, 1 study found a lack of consistent findings across both techniques. 149 This highlights the need for future research to establish a clearer difference in the diagnostic utility of each technique. Moreover, in addition to the architectural and microstructural changes highlighted with the use of DTI, magnetoencephalography has been used to identify changes in functional connectivity; patients with mTBI exhibited weakened local connections and strong long-range connections, displaying an inverse relationship relative to non-mTBI controls.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%